2015
DOI: 10.1007/s10336-015-1300-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in parental care in the spectacled tyrant Hymenops perspicillatus is associated with increased nest predation in grassland fragments

Abstract: Predation risk on birds is often an important source of natural selection that shapes parental care and may promote behavioral changes. Parents can often estimate certain risks and adjust their behavior to reduce the likelihood of nest predation. The fragmentation of habitats is one of the main consequences of loss of habitats, and in general, for birds breeding in smaller patches, their daily nest-survival rate is lower due to increased nest predation. Since nest survival is an estimate of predation risk in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
9
1
Order By: Relevance
“…Our data show that chickadees did not alter reproductive strategy later in the breeding attempt, consistent with the idea that response to house wren threat is flexible and stage-specific. While other studies show that presence of a general offspring predator (i.e., a predator that is also a threat to nestlings) may influence feeding rate (Chalfoun & Martin, 2010;Fontaine & Martin, 2006;Pretelli et al, 2016;Sofaer et al, 2012;Yoon et al, 2016;Zanette et al, 2011), we found no such differences. We found instead that variation in number of both total feeding trips and per nestling feeding trips was mostly explained by brood size: Larger broods had more total trips but fewer trips per nestling.…”
Section: F I G U R Econtrasting
confidence: 99%
See 3 more Smart Citations
“…Our data show that chickadees did not alter reproductive strategy later in the breeding attempt, consistent with the idea that response to house wren threat is flexible and stage-specific. While other studies show that presence of a general offspring predator (i.e., a predator that is also a threat to nestlings) may influence feeding rate (Chalfoun & Martin, 2010;Fontaine & Martin, 2006;Pretelli et al, 2016;Sofaer et al, 2012;Yoon et al, 2016;Zanette et al, 2011), we found no such differences. We found instead that variation in number of both total feeding trips and per nestling feeding trips was mostly explained by brood size: Larger broods had more total trips but fewer trips per nestling.…”
Section: F I G U R Econtrasting
confidence: 99%
“…Threats from predation can result in costly alterations in parental behavior throughout nesting (i.e., both egg and nestling stages) because general offspring predators are often relevant throughout the entire breeding attempt (e.g., Fontaine & Martin, ; Zanette, White, Allen, & Clinchy, ). In the presence of a threat, parents can alter behavior that results in reduced clutch size (Doligez & Clobert, ; Eggers, Griesser, Nystrand, & Ekman, ; Hua, Sieving, Fletcher, & Wright, ; Zanette et al, ), reduced clutch mass (Fontaine & Martin, ), changes in incubation behavior (Conway & Martin, ; Ferretti, Llambías, & Martin, ; Ibáñez‐Álamo & Soler, ; Massaro, Starling‐Windhof, Briskie, & Martin, ), and reduced nestling provisioning (Chalfoun & Martin, ; Dudeck, Clinchy, Allen, & Zanette, ; Fontaine & Martin, ; Pretelli, Isacch, & Cardoni, ; Sofaer, Sillett, Peluc, Morrison, & Ghalambor, ; Yoon, Kim, Joo, & Park, ; Zanette et al, ). Increased time off the nest during incubation results in eggs with decreased embryo mass, reduced residual yolk, and reduced growth efficiency (Olson, Vleck, & Vleck, ) and decreased nestling provisioning is associated with slower nestling growth and poorer quality nestlings (Scheuerlein & Gwinner, ; Thomson et al, ; Zanette et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Pretelli et al. ). In addition, experimental manipulation of perceived predation risk resulted in changes in the activity at the nest in several species (Kovařík and Pavel ; Ibáñez‐Álamo and Soler ; Basso and Richner ).…”
Section: Discussionmentioning
confidence: 97%